CO2 flux in a wheat‐soybean succession in subtropical Brazil: A carbon sink. Issue 5 (29th June 2022) - Veeck, Gustavo Pujol; Dalmago, Genei Antonio; Bremm, Tiago; Buligon, Lidiane; Jacques, Rodrigo Josemar Seminoti; Fernandes, José Maurício; Santi, Anderson; Vargas, Paulo Roberto; Roberti, Débora Regina
Abstract: The subtropical region of Brazil is home to 33% of the soybean [ Glycine max  (L.) Merr.] growing area and 90% of the wheat ( Tritucum aestivum L.) growing area of this country. A soybean–wheat succession with fallow between crops is used in about 11% of the cultivated area. No study has quantified CO2 fluxes in annual soybean–wheat succession in this region. Hence, this study analyzed the seasonality of CO2 exchange (net ecosystem exchange [NEE]) in a 2015/2016 wheat–soybean succession in a commercial farm located in Carazinho, Rio Grande do Sul State, Brazil. The eddy covariance method was used to estimate the annual C balance of this system. The NEE was partitioned between gross primary productivity and ecosystem respiration to understand the dynamics of these fluxes during a year of wheat–soybean succession. Considering the net ecosystem balance between photosynthesis and respiration during the growing season, both soybean and wheat absorbed CO2 from the atmosphere (NEE wheat: –347 ± 4 g C m –2 ; NEE soybean: –242 ± 3 g C m –2 ). The fallow periods between growing seasons, however, acted as a source of 156 ± 2 g C m –2, reducing the C absorbed by the crops by 27%. For 1 yr, the net biome productivity was –50 g C m –2  yr –1 . The results obtained here demonstrate that the wheat–soybean succession was a net C sink under these specific climatic conditions and field management practices and that the long fallow period between crops limited the agroecosystem from becoming a more efficient CO2 sink. Core Ideas: The CO2 exchange in a wheat–soybean succession in subtropical Brazil was evaluated. NEE was greater in the wheat than in the soybean growing season. The fallow periods emitted 27% of the NEE absorbed during the growing season. The wheat–soybean succession acted as a carbon sink (50 g C m–2 yr–1).